RESEARCH OF EXPEDIENCY OF INTRODUCTION OF BICYCLE INFRASTRUCTURE IN THE CITIES OF UKRAINE - Ходан, Владислав; Тарасенко, Олександр; Трушевський, В’ячеслав (SWorldJournal, 2022)
The paper considers the issues of active introduction of bicycle transport in the cities of Ukraine, the advantages of using bicycles as urban transport and proposals for the development of bicycle infrastructure.